Promotion of Lotus tenuis in the flooding Pampa (Argentina) increases the soil fungal diversity - Nieva, Amira Susana del Valle; Bailleres, Matias Andres; Llames, María Eugenia; Taboada, Miguel Angel; Ruiz, Oscar Adolfo; Menéndez, Ana Bernardina (2018)
Forage promotion is an increasingly used agricultural practice that requires herbicide application to remove competing plant species. This work examined the effect of the forage legume Lotus tenuis on the fungal community composition at three sites of the Flooding Pampa, Argentina. Replicate paddocks, managed either by herbicide-mediated promotion of L. tenuis or unmanaged (dominated by grasses) were compared using 454 pyrosequencing, targeting the fungal internal transcribed spacer (ITS) gene. Our results suggest that fungal diversity in the studied area varied according to the site and the land use (natural grasses vs. L. tenuis promotion). Several factors [pH, Ca2+, P, and HCO3−] were the main soil environmental drivers of distribution of fungal classes. Herbicide-mediated L. tenuis promotion led to increased fungal diversity, with dominance of Fusarium species.